Transfigurations Violence, Death and Masculinity in American Cinema - Grønstad, Asbjørn (Film Culture in Transition, 2008)
In many senses, viewers have cut their teeth on the violence in American cinema: from Anthony Perkins slashing Janet Leigh in the most infamous of shower scenes; to the 1970s masterpieces of Martin Scorsese, Sam Peckinpah and Francis Ford Coppola; to our present-day undertakings in imagining global annihilations through terrorism, war, and alien grudges. Transfigurations brings our cultural obsession with film violence into a renewed dialogue with contemporary theory. Grønstad argues that the use of violence in Hollywood films should be understood semiotically rather than viewed realistically; Tranfigurations thus alters both our methodology of reading violence in films and the meanings we assign to them, depicting violence not as a self-contained incident, but as a convoluted network of our own cultural ideologies and beliefs.